"Menelusuri Pergolakan Emosional pada Puisi “Tentang Mahasiswa yang Mati, 1996” - Mukafi, Muhammad Hamdan; Putra, Wahyu Kartika (Sabda: Jurnal Kajian Kebudayaan, 2022)
The poem "About Students Who Died in 1996" was included in Sapardi Djoko Damono's poetry anthology Ayat-Ayat Api. The anthology illustrates the atmosphere of the new order environment in Indonesia so that the poems contained therein carry an emotional message in the struggle for democracy. This research will focus on tracing the creation of emotional turmoil created in the poems. Thus, the purpose of this research is to (1) present a review of the development of empathetic emotions in poetry to create an aesthetic understanding, and (2) present a review of the relevance of poetry to its visualization (image 1). As the basis of analysis, the method used is descriptive qualitative method, with critical discourse analysis technique supported by empathy theory by Titchener and cognitive & affective empathy theory by Hoffman. The theory of empathy is used to determine the construction of cognitive empathy knowledge narratives that later lead to affective empathy and finally lead to intact knowledge about the aesthetics of the poems and images analyzed. The theory attempts to answer the mobilization and development of cognitive and affective empathy for the poem based on the events of Kudatuli 1996. The reader is also directed to know about the event in order to bring out the aesthetic understanding. With the visualization of images taken in the 20s, this research tries to construct the emotion of the poem's content.